THE SOCIAL AND POLITICAL ASPECTS OF NEW MEDIA (Menelusuri Jejak Kesadaran dan Tindakan Kolektif Massa) - Mauliansyah, Fiandy (Universitas Teuku Umar, 2016)
Managing broadcasting management is not easy. Managing the broadcasting business is a difficult and challenging. This research aims to analyze the activity of management and organizational performance ACEH TV television media in an effort to disseminate the Islamic Sharia and Preservation of Local Culture in Aceh. This research is descriptive qualitative. Informants of this research is managing director, program director, executive producer, cameraman / reporter, as well as additional informants Regional Chairman of the Indonesian Broadcasting Commission (KPID) Aceh, Aceh Province Department of Islamic Law, and local media observers. The location of this research is in Banda Aceh, Aceh province.Sampling was done purposively. Data collected through observation, interviews, and documentation. Data were analyzed by analysis of an interactive model of Miles and Huberman. The results showed that the ACEH TV as the medium of television that is broadcasting management ACEH have done according to a local television broadcasting standard. Agenda setting function of mass media performed in the ACEH TV dissemination of Islamic Shariah in Aceh and local culture to influence the people of Aceh to implement Islamic Sharia and also maintain the culture and local wisdom Aceh. It can be seen from all the programs that are aired ACEH TV is a program of local cultural nuances of Islamic law.There are still some shortcomings in running broadcasting broadcasting technology such as lack of equipment that is increasingly sophisticated. The results of image editing is very simple, and some programs presenter still looks stiff when in front of the camera.Â Keywords: Management of ACEH television,Islamic law,local culture Acehnese,agenda setting.